2021
DOI: 10.1016/j.ijid.2021.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Real-world clinical performance of commercial SARS-CoV-2 rapid antigen tests in suspected COVID-19: A systematic meta-analysis of available data as of November 20, 2020

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 32 publications
3
43
1
Order By: Relevance
“…However, while specificity is generally high, sensitivity is quite variable between different tests [46] . A recent meta-analysis on 19 clinical studies showed a reasonably good specificity, ranging from 92.4 to 100%, while sensitivity varied greatly, between 28.9 and 98.3% [47] . Therefore, such rapid tests can be useful for large-scale screening, but cannot generally substitute for molecular tests, including RT LAMP, except perhaps those few with the best performances.…”
Section: Discussionmentioning
confidence: 99%
“…However, while specificity is generally high, sensitivity is quite variable between different tests [46] . A recent meta-analysis on 19 clinical studies showed a reasonably good specificity, ranging from 92.4 to 100%, while sensitivity varied greatly, between 28.9 and 98.3% [47] . Therefore, such rapid tests can be useful for large-scale screening, but cannot generally substitute for molecular tests, including RT LAMP, except perhaps those few with the best performances.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the advantages and clinical performance of these rapid antigen test devices (Jungnick et al, 2021), and their data have shown favorable performance in detecting SARS-CoV-2 VOCs using rapid antigen testing. High sensitivities have been observed in high-viral-load samples using commercial rapid antigen tests (Hayer et al, 2021). However, N protein mutations in SARS-CoV-2 VOCs potentially lead to false-negative results with some rapid antigen tests, despite high viral load (Boehm et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The overall sensitivity of the Panbio RAD assay was 70.6%, which nevertheless was notably dependent upon the range of SARS‐CoV‐RNA loads in NP specimens, as it has been systematically reported for adults. 3 In fact, the sensitivity of the RAD assay reached 100% when only specimens with high viral load, specifically those returning RT‐PCR C T < 22, were considered for the analyses. Two large studies assessing the clinical performance at POC of the Panbio assay and strictly focusing on pediatric patients of all ages have been recently published yielding rather dissimilar results in terms of sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…1 Nevertheless, lateral flow immunochromatography‐based rapid antigen detection tests (RAD) have emerged as a routine diagnostic tool of COVID‐19 at the point‐of‐care (POC), as they are simple to perform, thus circumventing the need for special equipment and personnel qualification, and low cost. 2 Notable experience has been gathered as to the performance of SARS‐CoV‐2 RAD in adult patients presenting with clinically compatible COVID‐19, 3 in whom they have shown to display a variable sensitivity, ranging from 45% to 96%, largely depending on the range of SARS‐CoV‐2 load in the specimens tested, which ultimately relates to the timing of specimen collection since the onset of symptoms. There is sparse information on how RAD performs in children suspected of having COVID‐19.…”
Section: Introductionmentioning
confidence: 99%